Improvement of beef cattle through breeding - Smith, W.H.; Wheat, J.D.; Spies, H.G. (Kansas Agricultural Experiment Station, 2011)
The purebred Shorthorn beef cattle breeding experiment was initiated to study inheritance of production traits, to evaluate effects of inbreeding, and to explore the feasibility of using inbred lines for breeding improvement of production traits. The project was initiated in 1949 and was continued during 1965 according to plan.
Keywords: Beef; Breeding; Production traits; Inbreeding